Information System for Managing Goods and Web-Based Sales Transactions in Retail Businesses Using the Waterfall Method - Firdaus, Muhammad Ariq; Suharso, Wildan (ASTONJADRO, 2026)
The rapid development of information technology has created both opportunities and challenges for businesses, especially in the retail sector. In an effort to improve operational efficiency and service quality, information systems are an important requirement that cannot be ignored. Queen Cell and Queen Baby Shop, two retail business units operating in Tanggamus Regency, still run inventory management and sales transactions manually. The process often causes various problems such as delays in recording, stock mismatches, and financial report errors. To overcome these problems, this research designs and implements a web-based information system specifically designed for the needs of managing goods and sales transactions. The system development methodology uses the SDLC waterfall model approach because it is considered suitable for project needs with clear and stable specifications from the start. The system developed has two types of users, namely ad- min and employees, with the main features being product data management, transaction recording, and sales report processing. The imple- mentation results show that the system can run as expected and is able to significantly improve work efficiency and data accuracy. In addition, the system supports multi-platform access through the web so that it is flexible to use on various devices. It is hoped that this in- formation system can be a sustainable solution for small to medium scale retailers in facing the challenges of digitalization.